2013
DOI: 10.11114/ijsss.v1i2.200
|View full text |Cite
|
Sign up to set email alerts
|

The Social Transformation of Coffee Houses: The Emergence of Chain Establishments and the Private Nature of Usage

Abstract: Ray Oldenburg (1989) developed the concept of third places as environments that offer friendship and a sense of community. However, the idealized image of the coffee house may need revision. In recent decades coffee houses have transformed from small-scale businesses to corporate-owned franchises, and with the advent of personal electronic devices many people now use them to work rather than to socialize. Using unobtrusive observation data from three independently-owned and three chain-based coffee houses in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
(11 reference statements)
1
15
0
Order By: Relevance
“…They found that regardless of ownership, the widespread adoption of laptops, mobile phones, and tablets meant that coffeehouses have become multifunctional spaces where people work as well as socialize. Chain‐coffeehouses provided better office amenities than their independent counterparts, with more power outlets, large working surfaces, and free unlimited Internet access, while independent coffeehouses were more likely to make customers feel “at home with the presence of locally made furniture, art and even photography” (Woldoff and others , 217).…”
mentioning
confidence: 99%
“…They found that regardless of ownership, the widespread adoption of laptops, mobile phones, and tablets meant that coffeehouses have become multifunctional spaces where people work as well as socialize. Chain‐coffeehouses provided better office amenities than their independent counterparts, with more power outlets, large working surfaces, and free unlimited Internet access, while independent coffeehouses were more likely to make customers feel “at home with the presence of locally made furniture, art and even photography” (Woldoff and others , 217).…”
mentioning
confidence: 99%
“…As Laurier and Philo () and Woldorff et al . () also found, these are cafe spaces which people are using in multiple ways to work, escape, restore, eat, catch up, be alone, pass time. And these are part of daily routines, meaning customers become recognized and known by staff.…”
Section: Multiculture and MIX In The Semi‐public Franchised Cafe Spacesmentioning
confidence: 96%
“…For example, in their work comparing independent and branded cafe spaces Woldoff et al . found that although the ‘independent coffee houses offered local flavour that Starbucks does not’ (: 217) the Starbuck's cafes offered higher levels of sociality and were places in which staff chatted with customers ‘on a first name basis, were familiar with their regular orders and knew significant personal information about them’ (2013: 209).…”
Section: Multiculture Conviviality and Cafe Spacesmentioning
confidence: 99%
“…Not all ritual interactions need to be this monumental. Entrainment also occurs in everyday situations (see Goffman 1967), such as the kind of non-interactions that take place between the patrons of a café (see Woldoff et al 2013) as they seemingly ignore each other and go about their business, reading the paper, drinking their coffee, or working on their laptops. Nevertheless, those present in the café still contribute to the general atmosphere through their minute social signals, creating emotional attachments and interpersonal meanings.…”
Section: Ritual Entrainment and The Governance Of Emotionmentioning
confidence: 99%